Bcl-2 Family Proteins Regulate Apoptosis and Epithelial to Mesenchymal Transition by Calcium Signals - Wu, Yanjiao; Tang, Liling (Current Pharmaceutical Design, 2016)
Intracellular Ca2+ signal plays a major role in many cellular processes, such as apoptosis and epithelial to mesenchymal transition (EMT). The role of Ca2+ in apoptotic signaling has been investigated deeply over the past few decades. In recent years, it has made progress in the interactions of intracellular Ca2+ homeostasis with EMT. Besides, Bcl-2 family proteins as versatile regulators of cell apoptosis not only regulate Ca2+ signal, but also play an important role in the induction of EMT. In this review, we summarized the relations among intracellular Ca2+ concentration, apoptosis and Bcl-2 family proteins. We also discussed the functions of intracellular Ca2+ concentration and Bcl-2 family proteins in EMT. By taking into account these analyses; we proposed a hypothesis of cell death and survival controlled by calcium signal.
Keywords: EMT